INOVASI PEMBELAJARAN FIQIH BERBASIS KURIKULUM CINTA DI MADRASAH: STUDI KUALITATIF DI MTS NURUL UMMAH - Saputra, Amri; Wasith Achadi, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fiqh learning in madrasahs does not only aim to provide students with an understanding of Islamic legal principles but also to shape their character and religious attitudes. However, in practice, Fiqh learning often focuses primarily on cognitive mastery of the material and pays less attention to the internalization of moral values. This study aims to analyze the implementation of innovative Fiqh learning based on the Love-Based Curriculum at MTs Nurul Ummah. This research employed a qualitative approach with a field research design. Data were collected through interviews, observations, and documentation involving Fiqh teachers and the school principal as research informants. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that Fiqh learning integrates the principles of the Love-Based Curriculum through humanistic, dialogical, and contextual learning approaches. This implementation is reflected in the use of discussion methods, classical text explanation, case studies, and the utilization of various learning resources that are connected to students’ daily life experiences. This approach not only enhances students’ understanding of Fiqh material but also encourages the development of religious attitudes, empathy, social awareness, and responsibility in everyday life.